2017
DOI: 10.3892/etm.2017.4691
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of heat shock protein 60 on matrine-suppressed microglial activation

Abstract: Abstract. Matrine (MT) is the primary active alkaloid separated from members of the Sophora genus. Previous studies have reported that MT has anti-inflammatory effects in the central nervous system (CNS). However, the underlying molecular mechanism of the neuroprotective effect of MT remains unclear, particularly the role of heat shock protein 60 (HSP60). Microglia are macrophages in the CNS that serve an essential role in the innate immune system by producing various proinflammatory and neurotoxic factors. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Therefore, to explore potential mechanisms underlying the decrease in the HSP60 intracellular levels in curcumin-treated cells, we evaluated possible extracellular release. Other groups and we have already shown that HSP60 can be secreted by cells, in particular by cancer cells via both secretion canonical pathways and via exosomes [15,23,24,26,50,[64][65][66][67]. In this work, we demonstrated that HSP60 is secreted by LAN-5 cells after 24 h of treatment with 25 µM of curcumin.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, to explore potential mechanisms underlying the decrease in the HSP60 intracellular levels in curcumin-treated cells, we evaluated possible extracellular release. Other groups and we have already shown that HSP60 can be secreted by cells, in particular by cancer cells via both secretion canonical pathways and via exosomes [15,23,24,26,50,[64][65][66][67]. In this work, we demonstrated that HSP60 is secreted by LAN-5 cells after 24 h of treatment with 25 µM of curcumin.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, the extracellular release of Hsp60 increases the production of other pro-inflammatory factors through binding to toll-like receptor 4 (TLR-4) and stimulating neuronal cell death [ 55 ]. Over-activation of microglia in response to certain harmful factors, contributes to the progression of several neurodegenerative diseases, including AD [ 57 ]. Neurodegenerative diseases are associated with the secretion of various pro-inflammatory and cytotoxic factors by activated microglia in the brain [ 58 , 59 ].…”
Section: Hsp60mentioning
confidence: 99%
“…Neurodegenerative diseases are associated with the secretion of various pro-inflammatory and cytotoxic factors by activated microglia in the brain [ 58 , 59 ]. Therefore, inhibiting the activation of microglia and Hsp60 expression/release is an important strategy for the prevention of neurodegeneration [ 57 ]. Hsp60 levels were high in lymphocytes from AD patients when compared to controls [ 60 , 61 ].…”
Section: Hsp60mentioning
confidence: 99%
“…Interestingly, eHSPs, such as eHSP90, eHSP70, eHSP60, and eHSP27 might be highly expressed and released as "chaperokines", where they play a major role in inflammation and immunity [142,145,146]. However, dependent on the circumstances, the same HSP proteins are not as highly expressed and can be observed in lower amounts in the extracellular space, such as eHSP60 [147] and eHSP27 [148]. eHSPs can stimulate inflammatory cytokine release from immune cells [141,143], recruit Natural Killer (NK) cells [141], and activate microglial phagocytosis [70].…”
Section: Extracellular Hspsmentioning
confidence: 99%